2022
DOI: 10.1111/bjet.13245
|View full text |Cite
|
Sign up to set email alerts
|

Big data, big changes? The technologies and sources of data used in science classrooms

Abstract: With improving technology and monitoring efforts, the availability of scientific data is rapidly expanding. The tools that scientists and engineers use to analyse data are changing in response. At the same time, science education standards have shifted to emphasize the importance of students making sense of data in science classrooms. However, it is not yet known whether these exciting new datasets and tools are used science classrooms, and what it would take to facilitate their use. To identify opportunities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…When teachers did identify automation in lesson plans, they primarily incorporated it using spreadsheets to visualize data, similar to the findings of Rosenberg et al (2022). For example, the biology teachers frequently used spreadsheets in their lessons to help students create graphs (visualize) in order to look for trends.…”
Section: Characteristics Of Integration By Ct Practicementioning
confidence: 95%
See 1 more Smart Citation
“…When teachers did identify automation in lesson plans, they primarily incorporated it using spreadsheets to visualize data, similar to the findings of Rosenberg et al (2022). For example, the biology teachers frequently used spreadsheets in their lessons to help students create graphs (visualize) in order to look for trends.…”
Section: Characteristics Of Integration By Ct Practicementioning
confidence: 95%
“…Over time and repeated engagement, students may be able to distinguish how the phenomena they are studying relate to data representations (Laina & Wilkerson, 2016). Rosenberg et al (2022) noted that although teachers often use digital tools such as calculators and spreadsheets for students to analyze and make representations, there are more tools that can be used in classrooms to promote more sophisticated data analysis. Given how students can benefit from the use of certain aspects of data practices such as pattern recognition, there are opportunities to support student data practices with computational thinking.…”
Section: Data Practicesmentioning
confidence: 99%
“…Data collection and analysis are common practices in science classrooms. Rosenberg et al (2022) conducted a study to explore the data sources and tools that K-12 science teachers used in their classrooms. In terms of tools (and technologies), the study showed that teachers mainly chose to use general tools, namely Google Sheets and calculators.…”
Section: Contributions To the Speci Al Sectionmentioning
confidence: 99%
“…The global shock caused by COVID-19 created many challenges and risks for countries and regions. Digital tools showed their potential to provide innovations solutions for the unexpected turbulences caused by the pandemic, from digital tools for education (Mahmud et al , 2022; Rosenberg et al , 2022; Weilage and Stumpfegger, 2022; Yu, 2022) and innovative tools for the management of global value chains (Butollo et al , 2022; Cusumano et al , 2019; De Propris and Pegoraro, 2019; European Commission, 2023a; Yeung, 2021), to artificial intelligence (AI) and internet of things (IoT) for the health care (Ienca and Vayena, 2020; Lytras et al , 2009; Ordóñez de Pablos et al , 2022; Pretorius and Coyle, 2021; Zhang et al , 2015), for example. The transition toward a digital and green economy brings new challenges but also opportunities for the creation of jobs and boost competitiveness.…”
Section: Introductionmentioning
confidence: 99%